2016
DOI: 10.2344/0003-3006-63.2.84
|View full text |Cite
|
Sign up to set email alerts
|

Variant Inferior Alveolar Nerves and Implications for Local Anesthesia

Abstract: A sound knowledge of anatomical variations that could be encountered during surgical procedures is helpful in avoiding surgical complications. The current article details anomalous morphology of inferior alveolar nerves encountered during routine dissection of the craniofacial region in the Gross Anatomy laboratory. We also report variations of the lingual nerves, associated with the inferior alveolar nerves. The variations were documented and a thorough review of literature was carried out. We focus on the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 42 publications
1
23
0
2
Order By: Relevance
“…The risk of arterial damage during anaesthetic procedures is believed to be escalated due to proximity if maxillary artery with branches of mandibular nerve. 5 It has also been reported by Standring et et al that the inferior alveolar nerve block can be administered trans orally or by the external route through the skin of the face. 6 If there are variations involving formation of this nerve as found in the present report, this might interfere with producing the desired anaesthesia if administered via oral or subcutaneous routes.…”
Section: Department Of Anatomy University College Of Medical Sciencementioning
confidence: 92%
“…The risk of arterial damage during anaesthetic procedures is believed to be escalated due to proximity if maxillary artery with branches of mandibular nerve. 5 It has also been reported by Standring et et al that the inferior alveolar nerve block can be administered trans orally or by the external route through the skin of the face. 6 If there are variations involving formation of this nerve as found in the present report, this might interfere with producing the desired anaesthesia if administered via oral or subcutaneous routes.…”
Section: Department Of Anatomy University College Of Medical Sciencementioning
confidence: 92%
“…Anatomical factors comprise accessory nerve supply, alteration in foramen location, atypical development of the nerves (bifid mandibular canals), and bone density [39,40].…”
Section: Lack Of Effectmentioning
confidence: 99%
“…; Wolf et al. ), the number of bones in the cranium can vary due to occasional appearance of wormian (intra‐sutural) bones (Hess, ; Ghosh et al. ), and there are many more examples of unpredictable anatomy in anatomical and surgical literature.…”
Section: Introduction: the Paradox Of Anatomical Variationmentioning
confidence: 99%
“…One of the first things that medical students learn of human anatomy, usually to their frustration, is that its details are surprisingly variable. Blood vessels can vary in route and number (D aescu et al 2012;Bertrand et al 2014;Silva et al 2014;Marco-Clement et al 2016;Tomaszewski et al 2017), innervation of the same structure can differ between individuals (Matejc ık, 2010; Henry et al 2016;Wolf et al 2016), the number of bones in the cranium can vary due to occasional appearance of wormian (intrasutural) bones (Hess, 1946;Ghosh et al 2017), and there are many more examples of unpredictable anatomy in anatomical and surgical literature. Some of these differences may be specified genetically, but studies of monozygotic twins have demonstrated that histogenesis can vary even when driven by exactly the same 'genetic programme'.…”
mentioning
confidence: 99%